Barriers to the Adoption of Data Analysis tools - Noonpakdee, Wasinee; Satitsamitpong, Manit; Phothichai, Acharaphun; Khunkornsiri, Thitiporn (Journal of Applied Statistics and Information Technology, 2018)
Business Intelligence and data analysis has become a critical aspect for many organizations, and is considered as one of the key drivers for business growth. Data analysis tools can be functioned for dashboards, interactive report, statistic and data mining, localization, analysis, data management, data visualization, and sharing information. In spite of several benefits and functions of data analysis tools, there are some issues regarding the adoption of the tools. This research aims to study the barriers to the Adoption of Data Analysis tools focusing on small and medium-sized enterprises (SMEs). The research process consists of three stages: 1) Literature review 2) Observation and interview of 30 SMEs in Thailand, and 3) Analysis and conclusion. According to the results, barriers to the adoption of data analysis tools are technology barrier, data barrier, human barrier, and organization barrier. The approach to overcome these barriers is proposed. The result can be a guideline for the implementation of BI system to improve profitability and attain the competitive advantages in the organization.